Effectiveness of Balloon Tamponade with a Condom Catheter versus Using a Sengstaken-Blakemore Tube in Patients with Primary Postpartum Hemorrhage: Balloon Tamponade and Sengstaken-Blakemore for Postpartum Hemorrhage - Nisa, Shamas un; Javed, Aisha; Rehman, Mujeeb ur; Babar, Nadia (Pakistan Journal of Health Sciences, 2024)
Balloon tamponade or Sengstaken-Blakemore tube, are gaining fame because of its low complications, low invasiveness, rapid approach, painless removal, and rapid identification of failed cases in primary postpartum hemorrhage. Objective: To compare the efficacy of balloon tamponade versus Sengstaken-Blakemore tube in patients with primary postpartum hemorrhage. Methods: This comparative/cross-sectional was conducted at the department of Obstetrics and Gynaecology at Bahawal Victoria Hospital, Bahawalpur from July 2023 to December 2023. A total of 64 patients (32 in each group) females aged between 18 and 40 years of parity 1-6, gravida 1-6, gestational age 31 to 41 weeks, with primary postpartum hemorrhage were recruited. Females in balloon tamponade group underwent balloon tamponade, and those in Sengstaken-Blakemore tube group underwent Sengstaken-Blakemore tube insertion and balloon removal after 24 hours. The effectiveness was labelled as yes where there was no blood loss for 24 hours after the removal of the pack or foleys. Results: The mean age was 31.05 ± 5.92 years. The effectiveness of the treatment was observed among 51 (79.7%) females. In balloon tamponade group, mean blood loss was 787.81 ± 265.11 ml and 791.34 ± 254.78 ml in Sengstaken-Blakemore tube group. In balloon tamponade group, 29 (90.6%) patients had effectiveness of treatment while 22 (68.8%) females in Sengstaken-Blakemore tube group reported effectiveness (p=0.030). Conclusion: Tamponade with a balloon attached to a condom catheter were more successfully in stop bleeding after delivery of primary PPH cases.